The existence of inflammatory bowel lesions in gluten-sensitive enteropathy. Issue 648 (October 1979) - Kumar, P. J.; O'Donoghue, D. P.; Gibson, J.; Stansfeld, A.; Dawson, A. M.
Abstract : Three patients with coincident coeliac disease and inflammatory bowel disease are described. In 2 patients with known coeliac disease the recurrence of diarrhoea was not due to dietary deviation but to an additional large bowel pathology.